STRATEGI KOMUNIKASI UNIT BINMAS POLSEK SAMALANGA DALAM PENYULUHAN NARKOBA KEPADA MASYARAKAT DI KECAMATAN SAMALANGA - Syahputra, Edi (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
his research aims to provide counseling about drugs to the community in Samalanga sub-district. This research uses qualitative research using a descriptive approach. Data collection methods through interviews, observation and documentation using primary data, secondary data and assisted by informants. The results showed that the communication strategy of the Binmas unit of Samalanga Police in drug counseling was planning, organizing, implementing and evaluating. The effectiveness of the communication strategy of the Binmas unit of Samalanga Police in drug counseling shows that the success rate has not been fully achieved according to plan due to various obstacles and efforts to overcome the obstacles of the communication strategy is to evaluate starting from planning, organizing, implementing and evaluating so that the communication strategy of drug counseling to the community can be carried out as expected.